The Effect of Coupled Shoulder Girdle and Hip Extensor Strength Training on Sprint Performance and Ball Speed in Youth Field Hockey Players - Anyadike-Danes, Kechi (Auckland University of Technology, 2018)
Sprint performance is important in many team sports including field hockey. Despite this, so far no studies have examined the effect of strength training on sprint performance in this cohort. Previous studies in other sports have shown a positive association between the increases in lower body strength and improvements in sprint performance. An often overlooked aspect of sprinting is the role of the upper extremities in the sprint action. Another key skill in field hockey is shooting where a player’s ability can be evaluated based on ball velocity and the time taken to execute a shot. Similarly to sprinting no studies have examined the effect of strength training on ball speed in field hockey. Research looking at both sprinting and ball striking in other sports have highlighted the importance of both the shoulder girdle and hip extensor musculature. Therefore it was the aim of this thesis to ascertain whether strengthening the hip extensors and shoulder girdle specifically could improve both sprint performance and ball speed in youth hockey players and establish inter-relationships between sprint speed, ball velocity, shoulder girdle and hip extensor strength in hockey players. Chapter 3 presents the reliability for two novel isometric assessments, the isometric lateral pulldown (ILP) and isometric hip thrust (IHT), amongst 10 male participants with at least 2 years of structured resistance training. The IHT had a relatively small (6%) mean difference (MDiff) and effect size ([ES] 0.14) indicating moderate to good reliability between testing sessions. A test-retest intraclass correlation (ICC) of 0.97 in combination with a coefficient of variation (CV) of 7.3% indicated a small average variability. A small MDiff (4%) and ES (0.17) are indicators of good reliability for ILP’s inter-session performance. While an ICC of 0.9 and a CV of 8.1% indicated that the average variability between sessions was small. Using these methods Chapter 4 determined the relationship between impulse generated and both sprint and ball striking performance in 23 youth male secondary school representative youth field hockey players. No significant relationships were found between sprint times and either of the isometric strength measures. Significant (p=0.000) large and positive correlations (r=0.68) were found between forehand ball release speed and isometric hip thrust results. Significant (p=0.046) moderate and positive correlations (r=0.42) were found between forehand ball release speed and isometric lateral pulldown results. Significant (p=0.025) moderate and positive correlations (r=0.47) were found between reverse ball release speed and isometric hip thrust results. Chapter 5 investigated the effects of a five week specialised strength training programme, targeting the shoulder girdle and hip extensor, on sprint performance and ball speed in a group of 10 youth male secondary school representative youth field hockey players. The programme resulted in significant large and positive improvements in both isometric hip thrust (p=≤0.000, ES = 1.21, +52.6%) and isometric lateral pulldown (p=0.007, ES = 1.46, +63.4%) and non-significant trivial and small positive improvements in forehand and reverse ball speed respectively (p=0.813, ES = 0.09, +1.15%, p=0.303, ES = 0.27, 4.95%). However, significant small and negative decrements were experienced in 10-m (p=0.03, ES = 0.57, 2.67%), 30-m (p=0.016, ES = 0.44, 2.21%) and 40-m (p=0.016, ES = 0.43, 2.24%) sprint performance while non-significant (p=≤0.07) small and negative decrements (ES = 0.31, 1.55%) were found for 20-m. For this thesis it was determined that strengthening the shoulder girdle and hip extensors specifically may increase ball speed but not sprint performance in youth hockey players.
Keywords: Field hockey; Youth athlete; Ball speed; Sprint performance; Impulse